CERITA DONGENG DI PUSARAN ARUS DIGITAL: MEMBANGUN KOLEKSI FILM ANIMASI DIGITAL DI PERPUSTAKAAN SEBAGAI UPAYA MENGEMBANGKAN JIWA NASIONALISME - Indah Purwani (Perpustakaan Nasional RI, 2016)
Building a nation’s characteris not merely a government task. It is also the responsibility of teachers, parents and the whole society to play the role. These three elements have a significant role in building up a person’s character from his/her early ages until he/she becomes a grown-up person. In the era of virtual reality and digital environment, building a child’s character has become even more important. One of many ways to build up nationalism among children is by popularizing folk tales in order to avoid the loss of the spirit of nationalism and culture that containsnational and traditional values. Libraries as information resources have a large potential and an important role in the building of a nation’s character and the development of nationalism among children in early stages. The National Library of Indonesia with publishers, Indonesia Film Institution and digital animation studios can work together in collaboration to build a center for digital animation film collection as a form of implementation of the I 990 Deposit Act in order to make it more useful and efficient.